1965
DOI: 10.1128/jb.89.4.1104-1108.1965
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification by Corynebacterium nephridii

Abstract: Corynebacterium nephridii was found to reduce nitrate (contrary to the original description) at a rapid rate. In the conventional 0.1% nitrate broth, neither nitrite nor nitrate was detected after 24 hr. There was no assimilation of nitrate nitrogen, and the final product of nitrate reduction was nitrous oxide. Manometric studies and growth experiments indicated that the organism is incapable of reducing nitrous oxide. C. nephridii is gram-negative, grows on bile salts (5%) agar, EMB Agar, and MacConkey Agar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…It has been known for some time that the rate of synthesis of the denitrifying enzymes is inversely related to the availability of oxygen in all bacteria capable of denitrifying respiration (44,225). This relationship prevails upon production of the enzymes (i) by the many bacteria that reduce nitrate to nitrogen, (ii) by those few that do not reduce nitrate but reduce nitrite to nitrogen (34), and (iii) by the small number that reduce nitrate to nitrous oxide but no further (110,124,285). Nitrate concentrations of 0.1 to 0.5% and nitrite concentrations up to 0.05% are optimal for growth of several denitrifying soil isolates in various types of media (19).…”
Section: Lookedmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for some time that the rate of synthesis of the denitrifying enzymes is inversely related to the availability of oxygen in all bacteria capable of denitrifying respiration (44,225). This relationship prevails upon production of the enzymes (i) by the many bacteria that reduce nitrate to nitrogen, (ii) by those few that do not reduce nitrate but reduce nitrite to nitrogen (34), and (iii) by the small number that reduce nitrate to nitrous oxide but no further (110,124,285). Nitrate concentrations of 0.1 to 0.5% and nitrite concentrations up to 0.05% are optimal for growth of several denitrifying soil isolates in various types of media (19).…”
Section: Lookedmentioning
confidence: 99%
“…In addition, a limited number of bacteria can reduce nitrate to elemental nitrogen by a series of anaerobic respiratory processes that, in sum, are called denitrification. In several studies, nitrite, nitric oxide, and nitrous oxide have been identified as intermediate products (12,166,224,225), although nitrous oxide rather than nitrogen is the terminal product of denitrification in a few bacterial species and strains (110,124,285).…”
Section: Introductionmentioning
confidence: 99%
“…A wide diversity of bacteria and archaea (>60 genera) and even some eukaryotes are capable of denitrification, the vast majority of which catalyze complete denitrification with N 2 as the final product (Zumft & Kroneck, 2007). Micro-organisms with truncated denitrification pathways that terminate with N 2 O have been known for several decades (Hart et al, 1965), and genomics has revealed that this phenotype can result from mutations in the N 2 O reductase (nos) genes or from the complete absence of nos genes (Zumft & Kroneck, 2007). In geothermal environments, a wide variety of thermophiles can respire nitrate or nitrite, including both Crenarchaeota (Völkl et al, 1993;Blöchl et al, 1997;Afshar et al, 1998) and…”
Section: Introductionmentioning
confidence: 99%
“…This study was undertaken to characterize the general features of denitrification by Corynebacterium nephridii. This organism was chosen for investigation because it possesses a unique denitrifying system, inasmuch as growing cells reduce nitrate to nitrous oxide (4). It was hoped that knowledge gained with this organism would aid in evaluating the pathway of dissimilatory nitrate reduction in other bacterial species.…”
mentioning
confidence: 99%